Strategic Management Competitiveness & Globalization : Concepts and Cases - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E.; Harrison, Jeffrey S. (Cengage, 2024)
Examine strategic management with the market-leading book that sets the standard as today's most intellectually rich, but practical analysis of strategic management. Written by award-winning instructors and prominent management scholars, Hitt/Ireland/Hoskisson/Harrison's STRATEGIC MANAGEMENT: COMPETITIVENESS AND GLOBALIZATION, 14E incorporates cutting-edge research and examples from more than 600 companies. This edition combines a classic industrial organization model with a resource-based view of the firm and a stakeholder perspective to demonstrate how businesses establish competitive advantages in the global market. You study how firms govern themselves, formulate and implement strategies that create value for stakeholders, use strategic alliances to enhance global competitiveness and meld strategic management and entrepreneurial behaviors for winning growth strategies.